2018
DOI: 10.1111/1471-0528.15475
|View full text |Cite
|
Sign up to set email alerts
|

External cephalic version at term: a cohort study of 18 years’ experience

Abstract: External cephalic version can safely be performed with most breech presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 34 publications
6
63
8
1
Order By: Relevance
“…Not surprisingly, both were associated with polyhydramnios and multiparity, which is in accordance with previous studies. 9,15 Nearly 91% of women with a successful ECV delivered vaginally, representing a remarkably low cesarean delivery rate of 9% compared to that reported in a recent meta-analysis. 38 This could be possibly explained by local hospital antepartum and intrapartum practice and a relatively high number of parous women.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Not surprisingly, both were associated with polyhydramnios and multiparity, which is in accordance with previous studies. 9,15 Nearly 91% of women with a successful ECV delivered vaginally, representing a remarkably low cesarean delivery rate of 9% compared to that reported in a recent meta-analysis. 38 This could be possibly explained by local hospital antepartum and intrapartum practice and a relatively high number of parous women.…”
Section: Discussionmentioning
confidence: 96%
“…5,6 Published series and meta-analyses have generally focused on ECV success rates, safety, and factors associated with the procedure's outcome. [7][8][9][10][11][12][13][14][15][16] Yet, an experience of a single operator that eliminates practice variations as a confounding factor in ECV success has been understudied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cambridge study, the uptake of ECV among eligible women was 65% and this was successful in only 14% of cases. In contrast, in the Oxford study, in which all women with breech presentation were managed in a specialist clinic, the uptake of ECV among eligible women was 90% and this was successful in 49% of cases. In relation to the timing of ECV, a Cochrane review of three trials reported that the success rate is higher if ECV is carried out at 34–35 weeks' gestation, rather than at 37–38 weeks, but at the expense of a higher rate of preterm birth.…”
Section: Discussionmentioning
confidence: 96%
“…A more realistic estimate of the accuracy of routine clinical examination in the detection of non‐cephalic presentation is 44%, as reported in a study from Cambridge, UK 27 . Additionally, a study from Oxford, UK, reported that ultrasound examination confirmed non‐cephalic presentation in only 41% of 7775 pregnancies suspected of breech presentation during routine antenatal care.…”
Section: Discussionmentioning
confidence: 99%